2014
DOI: 10.1007/s00024-014-0996-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Cloud and Convective Processes in Simulating the Weaker Tropical Cyclones over Indian Seas

Abstract: This study addresses the problem of incorporating moist processes (resolving the grid scale and parameterizing the subgrid scale) at resolutions of 9 and 3 km with double-and triplenested domains, respectively, in predicting the track and intensity of four cases of weaker tropical cyclones over the North Indian Ocean. The sensitivity experiments are carried out with three convective parameterization schemes, and the results are evaluated based on the track and intensity of cyclones. The Betts-MillerJanjic sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…These weak cyclones, due to their slow motion and quasi-stationary feature, cause very heavy rainfall and in turn large amount of damage to the property. Kanase et al (2014) suggested that convective adjustment scheme such as BMJ works better for relatively weak intensity storms. Mandal et al (2004) in their sensitivity study for two BoB cyclones using MM5 model, have shown that GD or BMJ works better in simulating track and intensity of cyclones.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These weak cyclones, due to their slow motion and quasi-stationary feature, cause very heavy rainfall and in turn large amount of damage to the property. Kanase et al (2014) suggested that convective adjustment scheme such as BMJ works better for relatively weak intensity storms. Mandal et al (2004) in their sensitivity study for two BoB cyclones using MM5 model, have shown that GD or BMJ works better in simulating track and intensity of cyclones.…”
Section: Introductionmentioning
confidence: 98%
“…Very few studies have focused on simulating the weak intensity storms (Osuri et al 2013;Srinivas et al 2013, Kanase et al 2014), but the detailed reasoning behind the success or failure of physical parameterization is hardly addressed. Further, it is essential to know which factor has more impact on cyclone's intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The schemes which showed rapid intensification process during the model simulation showed minimum deviation from the observed track, whereas the schemes which showed a slower intensification process during the model simulation showed maximum deviation from the observed track [45]. The intensity of the TC cyclone is influenced by the auto conversion process between the hydrometers and the amount of latent heat released during the conversion process [46,47]. To assess the impact of various microphysical schemes on the intensity of TCs, the vertical profile of the area averaged mixing ratios was calculated at every 3-hour interval over the entire numerical domain.…”
Section: Track and Intensity Errorsmentioning
confidence: 99%
“…Therefore, the WSM3 scheme produced a higher intensity for the cyclones Nilofar, Daye, Kyant, and Phethai. The intensity of the TC cyclone is influenced by the auto conversion process between the hydrometers and the amount of latent heat released during the conversion process [46,47]. To assess the impact of various microphysical schemes on the intensity of TCs, the vertical profile of the area averaged mixing ratios was calculated at every 3-hour interval over the entire numerical domain.…”
Section: Track and Intensity Errorsmentioning
confidence: 99%
“…The aforementioned studies indicated that the distribution of MP processes/hydrometeors plays a critical role in cyclone intensification, including rapid intensity changes and their dependency on moisture availability. However, various sensitivity studies are available over the NIO that focus on the overall track and intensity simulation and its relation with MP processes over the BoB region (Deshpande et al ., 2012; Kanase et al ., 2015; Maw and Min, 2017; Chutia et al ., 2019; Mohan et al ., 2019). Most studies conclude that the TC track is relatively insensitive to MP processes, but there is likely a distinct impact on the intensity simulations as outlined in recent studies.…”
Section: Introductionmentioning
confidence: 99%